PENGGUNAAN MEDIA GAMBAR DALAM MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA SEKOLAH DASAR (STUDI LITERATUR) - Risma Syifa Fauziah; Shinta Nurhalimah; Juhana Sakmal; Engga Dallion (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to describe the use of image media in improving student learning outcomes, especially in mathematics subjects. This research uses a literature review type of research with the review model chosen being a narrative review. The research design used is a qualitative research method with the data source used in the form of secondary data obtained from several accredited national journals, articles and previous research. Based on data from 10 journal articles that have been analyzed, it can be concluded that image media has a positive impact on mathematics learning in elementary schools, which is shows by an increase in students' mathematics learning outcomes in several elementary schools in Indonesia, both in low and high grades.